On the removability of isolated singularities of Orlicz – Sobolev classes with branching - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
The local behavior of closed-open discrete mappings of the Orlicz – Sobolev classes in R^n, n ≥ 3, is investigated. It is proved that the indicated mappings have continuous extensions to an isolated boundary point x_0 of the domain D { x0}, whenever the n - 1 degree of its inner dilatation has FMO (finite mean oscillation) at this point and, in addition, the limit sets of f at x_0 and D are disjoint. Another sufficient condition for the possibility of continuous extension can be formulated as a condition of divergence of a certain integral.